Trend and Contestation of Religious Discourse Post “Perppu Ormas” at Islamic College Jambi - Ahmad, Jafar; Mahmud Wafi; Hayat, Ade Putra; Herdiawanto, Heri; Hidayat, Taufiq (Institut Agama Islam Negeri Madura, 2022)
Government Regulation instead of Law (Perppu) for Ormas No. 2 of 2017 has shown its implications for religious activities and discourses at IAIN Kerinci and UIN Sultan Thaha Saifuddin Jambi. The argument of this research departs from the tendency of campus elements to strengthen identity through discourse contestation after the issuance of the Perppu Ormas. This study applies a descriptive qualitative approach through observation, interviews, and document review. This study found that Perppu Ormas No. 2 of 2017 raises two different attitudes at the level of student organizations. Acceptance of the Perppu Ormas argues intending to deradicalize and strengthen moderation. Meanwhile, the voices of refusal argued that the Perppu Ormas have the potential to weaken democracy and be misused. Perppu Ormas at the leadership level was welcomed by intensifying the discourse on religious moderation and strengthening the Pancasila ideology through seminars and study centers.